A new species of pitviper of the genus Protobothrops from China (Squamata: Viperidae) - Yang, Jian-Huan; Orlov, Nikolai L.; Wang, Ying-Yong (Zootaxa, 2011)
A new species of pitviper, Protobothrops maolanensis sp. nov. is described from the forested karst region in Maolan National Nature Reserve, Guizhou, China based on scalation, body proportions and color pattern. Data on the natural history of the new species are provided and a new key to the currently recognized species of Protobothrops is given. The new discovery and other recent findings suggest that further research is desirable in the karst regions in southern China and adjacent Vietnam, Laos and Myanmar.